After the wall : Germany, the Germans and the burdens of history - Fisher, Marc (Simon & Schuster, 1995)
The reunited Germany that emerged from the euphoria of 1989 - that miraculous moment when the Wall fell and all the world cheered - is neither a power to be feared nor a rich, stable democracy to be admired. Far from freeing the Germans from the burdens of history, the fall of the Wall has exacerbated the traumas of the past, leaving Germany divided - against itself, east from west: against the "other," its own six million foreign residents as well as hundreds of thousands of new immigrants who arrive each year; and most of all, against the continuing legacy of the Nazi and communist eras. The readmission of sixteen million East German residents has uncovered old wounds and lifted half a century of taboos. Blending essay and reportage and drawing on countless interviews with people from all sides, Marc Fisher tells stories that reveal a seething and chaotic nation handicapped by its past and struggling to define its role at home and abroad. These personal stories touch on the lingering fear of a mighty Germany, memories of the Holocaust, Germany's economic role as the engine of Europe, and its diplomatic role as the strongest nation at the border of the troubled former Soviet Bloc.